2013
DOI: 10.1177/0272431613511330
|View full text |Cite
|
Sign up to set email alerts
|

Changes in School Connectedness and Deviant Peer Affiliation Among Sixth-Grade Students From High-Poverty Neighborhoods

Abstract: This longitudinal study examined associations between changes in School Connectedness and changes in Affiliation With Deviant Peers among students from high-poverty backgrounds during the year immediately following the transition to middle school. Sixth-graders (N = 328) attending two middle schools in a large school district completed measures of School Connectedness and Affiliation With Deviant Peers at three points across the year. Results from parallel process modeling showed that students’ reports of Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 63 publications
0
17
0
1
Order By: Relevance
“…Related to peer factors, one study found that peer selection effects in aggression were more pronounced from the middle (winter) to end of the school year as opposed to other time points (Logis, Rodkin, Gest, & Ahn, 2013). In contrast, another study found no seasonal variations in peer influence (Rudasill, Niehaus, Crockett, & Rakes, 2014). More frequent observations are needed to capture relations between adolescent behaviors and peer factors (Chan & Poulin, 2007), and to explore seasonal variations in patterns of relations.…”
Section: Patterns Of Peer Behavior and Attitudes Over Timementioning
confidence: 99%
“…Related to peer factors, one study found that peer selection effects in aggression were more pronounced from the middle (winter) to end of the school year as opposed to other time points (Logis, Rodkin, Gest, & Ahn, 2013). In contrast, another study found no seasonal variations in peer influence (Rudasill, Niehaus, Crockett, & Rakes, 2014). More frequent observations are needed to capture relations between adolescent behaviors and peer factors (Chan & Poulin, 2007), and to explore seasonal variations in patterns of relations.…”
Section: Patterns Of Peer Behavior and Attitudes Over Timementioning
confidence: 99%
“…School connectedness has been associated with several positive outcomes, including health and well‐being (Jose, Ryan, & Pryor, ) and academic achievement (Skinner & Pitzer, ; Wang & Eccles, ). Additionally, lack of connectedness has been associated with negative behaviors and outcomes, including school failure and dropout (Archambault, Janosz, Fallu, & Pagani, ; Li & Lerner, ), substance use (Wormington, Anderson, Schneider, Tomlinson, & Brown, in press), depression (Shochet et al., ), delinquency (Chen, Voisin, & Jacobson, ; Rudasill, Reio, Stipanovic, & Taylor, ), and affiliation with deviant peers (Denny et al., ; Rudasill, Niehaus, Crockett, & Rakes, ).…”
Section: School Connectednessmentioning
confidence: 99%
“…Individuals with higher level of stress might experience school interest reduction, and then are less likely to be involved in school activities. School engagement was inversely correlated with deviant peers who have shown risky behaviors . The role of school interest in this relationship is potentially related to the fact that high school students with higher level of stress may not experience their happiness in learning and then lose their school interest.…”
Section: Discussionmentioning
confidence: 99%
“…School engagement was inversely correlated with deviant peers who have shown risky behaviors. 46 The role of school interest in this relationship is potentially related to the fact that high school students with higher level of stress may not experience their happiness in learning and then lose their school interest. The reduction of school interest is linked with less school involvements.…”
Section: School Interest Mediated the Association Between Stress Andmentioning
confidence: 99%